The characteristics and performance of hybrid redox flow batteries with zinc negative electrodes for energy storage. (July 2018) - Arenas, Luis F.; Loh, Adeline; Trudgeon, David P.; Li, Xiaohong; Ponce de León, Carlos; Walsh, Frank C.
Abstract: Zinc negative electrodes are well known in primary batteries based on the classical Leclanché cell but a more recent development is the introduction of a number of rechargeable redox flow batteries for pilot and commercial scale using a zinc/zinc ion redox couple, in acid or alkaline electrolytes, or transformation of surface zinc oxides as a reversible electrode. The benefits and limitations of zinc negative electrodes are outlined with examples to discuss their thermodynamic and kinetic characteristics along with their practical aspects. Four main types of redox flow batteries employing zinc electrodes are considered: zinc-bromine, zinc-cerium, zinc-air and zinc-nickel. Problems associated with zinc deposition and dissolution, especially in acid media, are summarized. The main features of each battery are identified and the benefits of a flowing electrolyte are explained. In each case, a summary of their development, the electrode and cell reactions, their potentials, the performance of the positive and negative electrodes, the advantages of a single flow compartment and cell developments for energy storage are included. Remaining challenges are highlighted and possibilities for future advances in redox flow batteries are suggested. Graphical abstract: fx1 Highlights: The importance of Zn negative electrodes for RFBs is highlighted. Acidic, neutral and alkaline electrolytes are involved. Zn- Br2, Zn-air, Zn-Ce, Zn-Ni and other Zn-based cells are featured. Electrode potentials and charge-discharge performance are considered. Developments are critically discussed; further R & D needs are underlined.